Pengaruh Deklinasi Dan Asensiorekta (Ra) Matahari Terhadap Suhu Ekstrim Di Sumatera Barat Tahun 2020-2024 - Aditya Zein Oktavianto; Letmi Dwiridal; Harman Amir; Hidayati Hidayati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates the influence of solar declination and right ascension on extreme temperature variability in West Sumatra during the 2020–2024 period using a quantitative empirical framework. Monthly climatological observations were integrated with astronomical parameters calculated through high-precision algorithms to construct a harmonically structured time series dataset. The results reveal that solar declination primarily governs the amplitude of seasonal temperature variation, while right ascension regulates temporal synchronization, producing observable phase shifts between astronomical forcing and atmospheric response. Harmonic analysis demonstrates that these relationships extend beyond linear correlations by capturing periodic patterns characterized by amplitude and phase metrics. Furthermore, residual components indicate the presence of external modulators, particularly sea surface temperature anomalies and large-scale climate variability, which alter the magnitude and timing of extreme temperature events. The combined analytical approach confirms that tropical atmospheric dynamics are shaped by interactions between deterministic astronomical cycles and stochastic environmental influences, offering a more robust basis for predictive climatological modeling and advancing the understanding of solar–atmosphere coupling in equatorial regions.